The Translation of Euphemism in the Novel “Fifty Shades Of Grey” - Yusuf, Hannisa Mawaddah; Ardi, Havid (English Language and Literature, 2024)
This research analyzed the translation of euphemism in the novel Fifty Shades of Grey (2011). This research aimed to find the types of euphemisms and the translation technique used by the translator in the novel Fifty Shades of Grey and wanted to know the impact of translation technique on euphemism results in TT. The euphemism types were analyzed using Allan and Burridge’s (2020) theory, classifying euphemisms into metaphor, hyperbole, idiom, litotes, circumlocution, acronym, shortening, indirection, and borrowing. Then, the translation technique was analyzed by using Molina and Albir’s (2002) theory as follows: borrowing, calque, literal translation, compensation, transposition, description, modulation, amplification, adaptation, established Equivalent, general translation, particularization, reduction, discursive creation, substitution, linguistic compression, linguistic amplification, and variation. The finding shows that the established Equivalent was the most dominant translation technique used by the translator to translate the euphemism types in the novel Fifty Shades of Grey into Indonesia. It also shows that the technique of translation affected the categories of euphemism translation results; if the types of euphemisms are translated with literal translation techniques, the meaning of euphemism becomes lost.